2021
DOI: 10.2196/33509
|View full text |Cite
|
Sign up to set email alerts
|

Central COVID-19 Coordination Centers in Germany: Description, Economic Evaluation, and Systematic Review

Abstract: Background During the COVID-19 pandemic, Central COVID-19 Coordination Centers (CCCCs) have been established at several hospitals across Germany with the intention to assist local health care professionals in efficiently referring patients with suspected or confirmed SARS-CoV-2 infection to regional hospitals and therefore to prevent the collapse of local health system structures. In addition, these centers coordinate interhospital transfers of patients with COVID-19 and provide or arrange speciali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The benefits resulting from implementing projects and telemedicine solutions are visible in the highly developed and developing countries. Research supports the idea that telemedicine is at least as good as conventional services, in terms of effectiveness, cost, and patient outcomes [ 25 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. The use of telemedicine tools as an alternative to traditional healthcare services has positively influenced the participants in the healthcare sector.…”
Section: Discussionmentioning
confidence: 89%
“…The benefits resulting from implementing projects and telemedicine solutions are visible in the highly developed and developing countries. Research supports the idea that telemedicine is at least as good as conventional services, in terms of effectiveness, cost, and patient outcomes [ 25 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. The use of telemedicine tools as an alternative to traditional healthcare services has positively influenced the participants in the healthcare sector.…”
Section: Discussionmentioning
confidence: 89%
“…In March 2020 the responsible government institution (Saxon Ministry of Social Affairs), divided Saxony into three COVID-19 coordination clusters—Chemnitz, Dresden and Leipzig 3 . One hospital (University Hospital Dresden, University Hospital Leipzig and the Hospital Chemnitz) in each cluster served as a central coordinator for SARS-CoV-2 patients and as a contact for outpatient and inpatient stakeholders in the healthcare system as well as for public health authorities 4 . Up to that point, direct data exchange and communication between hospitals were not standard.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 73 studies were validity studies (n=70) [25-34, 37, 39, 43-46, 48, 49, 51, 52, 56-58, 60, 62-66, 69, 70, 75, 77-79, 81-85, 87-91, 94-97, 99, 101-103, 105-112, 114-117, 119-122, 124, 125] or usability studies (n=3) [59,67,68] assessing a single method or tool, and 30 studies performed comparative analyses of different methods or tools [12, 35, 36, 38, 40-42, 47, 50, 53-55, 61, 71-74, 76, 80, 86, 92, 93, 98, 100, 104, 108, 113, 118, 126, 127]. Few studies prospectively evaluated methods or tools in a real-world work ow (n=20) [12,27,32,35,46,50,67,68,77,78,88,90,94,98,105,108,112,114,125,127], 7 studies of those used independent testing (by a different reviewer team) with external data [12,35,46,94,98,112,127].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies evaluated methods or tools for supporting the tasks of title and abstract screening (n=42) [32, 35, 36, 38, 43-45, 47, 48, 51, 55, 58, 59, 63, 73, 79, 82-84, 86-90, 94-96, 100, 102, 105-108, 112-114, 117-120, 125, 127] or devising the search strategy and performing the search (n=24) [28, 34, 37, 39, 42, 52, 53, 56, 60, 64-66, 72, 81, 91-93, 98, 99, 104, 110, 121, 122, 126] (see Figure 2). For several steps of the SR process, only a few studies that evaluated methods or tools were identi ed: deduplication: n=6 [30,36,54,57,71,80], additional search: n=2 [33,97], update search: n=6 [36, 50,61,77,109,111], full-text selection: n=4 [85, 113,114,125], data extraction: n=11 [31,36,46,67,69,70,74,103,112,124,125]; critical appraisal: n=9, [26, 27,36,49,62,68,75,101,115], and combination of abbreviated methods/tools: n=6 [12,25,76,78,100,116] (see Figure 2). No studies were found for some steps of the SR...…”
Section: Resultsmentioning
confidence: 99%